2009
DOI: 10.2214/ajr.08.1670
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Imaging of Mucinous Carcinoma of the Breast: Evaluation of Apparent Diffusion Coefficient and Signal Intensity in Correlation With Histologic Findings

Abstract: Mucinous carcinoma can be clearly differentiated from other breast tumors on the basis of ADC. The low signal intensity of mucinous carcinoma on diffusion-weighted images appears to reflect the presence of mucin and low cellularity. High signal intensity on diffusion-weighted images may reflect the presence of fibrovascular bundles, increased cell density, or a combination of these features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
105
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(126 citation statements)
references
References 19 publications
16
105
2
3
Order By: Relevance
“…Woodhams et al measured higher ADC values in mucinous carcinomas in comparison to other malignant lesions. In their study pure mucinous carcinomas had even higher ADC values than the majority of benign lesions [24]. In our study both pure type mucinous carcinomas revealed ADC values not noticeably different from benign lesions ( • " Fig.…”
supporting
confidence: 58%
“…Woodhams et al measured higher ADC values in mucinous carcinomas in comparison to other malignant lesions. In their study pure mucinous carcinomas had even higher ADC values than the majority of benign lesions [24]. In our study both pure type mucinous carcinomas revealed ADC values not noticeably different from benign lesions ( • " Fig.…”
supporting
confidence: 58%
“…The single mucinous carcinoma identified in our study had a higher mean ADC than the other types of breast cancers, even some of the benign lesions. This is consistent with the results of previous studies (Woodhams et al, 2009;Kul et al, 2011). Altough, the reason is not clear in the literature, there are other studies that showed similar low ADC values in fat necrosis as presented in our study (Kul et al, 2011;Fornasa et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…In this special type of breast cancer, the presence of both low cellularity and mucin-rich compartments has been proposed to be responsible for this higher ADC value (Woodhams et al, 2009). The single mucinous carcinoma identified in our study had a higher mean ADC than the other types of breast cancers, even some of the benign lesions.…”
Section: Discussionmentioning
confidence: 99%
“…19 One reason our results diŠer may be because they included special type breast cancers other than IDC, but we excluded such special types. For example, mucinous carcinomas show higher ADC values than IDC, 7,20 but lymph node metastasis of mucinous carcinoma of the breast is rare. 21 DiŠerences in tumor size might also aŠect the results, but Kim's group did not detail tumor size.…”
Section: Discussionmentioning
confidence: 99%